Effectiveness of peer-mediated Lego® play for reducing anxiety in children aged 4 to 6 years with and without Autism Spectrum Disorder: A scoping review - Mc Guckin, Conor; Wai-Wan Choy, Stella; Twomey, Miriam (ProudPen, 2024)
This research evaluated the effectiveness of peer-mediated Lego® play for reducing anxiety for children aged 4 to 6 years, including children with learning disabilities. Specifically, the research sought to identify the risk factors of anxiety disorders, and to explore how peer-mediated approaches using Lego®-Based Therapy might evidence a reduction in risk factors (i.e., prevention) and reduce challenges (i.e., early intervention) of anxiety in children. The methodology was designed “a priori” as a mixed methodology study, encompassing evaluation and case studies (i.e., standardised assessments, interviews, observations, questionnaires, visuals). Children are facilitated as co-participants, thus simultaneously providing an operational expression of the philosophy of “voice” (e.g., UN Article 12) for children in decisions of importance to them, within a Universal Design for Learning (UDL) framework. All sessions will be recorded for the Statistical Analysis of Change. Treatment fidelity will be included to measure change. This research makes a valuable contribution to knowledge in the area of early intervention and inclusive education. It expands the scope of Universal Design by applying a UDL framework to early intervention. It also proposes an overarching framework to place children in their bio-ecological context and incorporating children’s voices and neurodiversity, contributing to Hong Kong, Ireland and beyond.
Learning disabilities in the 21st century: Improving students achievements
PUBLISHED
London
Keywords: Anxiety; Learning Disabilities; Early Intervention; Inclusion; Lego®-Based Therapy